A distributed content repositories model and a decisions support system for learning objects in Latin-America - Cobos, Carlos; Meza, Erwin; Mendoza, Martha; Moreno, Jorge; Muñoz, Norman (Revista Colombiana de Computación, 2006)
This paper describes a content object and metadata repositories model, which provides an alternative to search and to access repositories developed in Colombia and Latin America. Along with the repositories model, an initial design of a decision support system for repositories is presented. In order to preserve the autonomy of each repository, a common web services interface is considered.